Geophysical Assessment of Coastal Aquifers and Seawater Intrusion Risk Around Vannamei Shrimp Farming Areas in Banyuwangi Regency, Indonesia - Ervina Wahyu Setyaningrum; Shinta Hiflina Yuniari; Agustina Tri Kusuma Dewi (Faculty of Fisheries and Marine Universitas Airlangga, 2026)
Graphical Abstract Highlight Research 1. Assessment of aquifer potential around vannamei shrimp ponds on the coast of Banyuwangi Regency. 2. Lithology along the coast of Banyuwangi Regency. 3. Estimation of groundwater potential around vannamei shrimp ponds on the coast of Banyuwangi Regency. 4. Aquifer depth, which is related to seawater intrusion based on aquifer layer color. Abstract The coast of Banyuwangi Regency is an area with high human activity involving the use of groundwater in aquifers, including activities related to vannamei shrimp farming. Therefore, seawater intrusion is suspected to occur, given that this area is adjacent to the sea. To assess the potential (distribution and depth) of the aquifer and the suspected seawater intrusion around the vannamei shrimp farming area. This approach is new because the aquifer assessment is conducted around the vannamei shrimp farming area as a basis for sustainability, especially in relation to the estimated seawater intrusion around the area. Data was collected through surveys and direct observation, by dividing the measurement area vertically and horizontally. Detection was carried out using AIDU Golden Rod (AGR), including data analysis using AIDU Prospecting software. The results of the study indicate that the productivity of aquifers around vannamei shrimp ponds in Banyuwangi Regency, for water discharge between < 5 L/second and > 10 L/second, and aquifer depths ranging from 5 to 200 m, shows indications of seawater intrusion around vannamei shrimp farms. The aquifer zone includes moderate to high productivity stretching along the geological structure, where low-resistivity AGR anomalies suggest possible salina/brackish zones; hydrochemical validation required. Therefore, further research is needed on the analysis of seawater intrusion values as a basis for sustainable groundwater management policies.